Assessment of vitamin D intake among Libyan women – adaptation and validation of specific food frequency questionnaire. Issue 1 (1st January 2018) - Faid, Fathia; Nikolic, Marina; Milesevic, Jelena; Zekovic, Milica; Kadvan, Agnes; Gurinovic, Mirjana; Glibetic, Marija
ABSTRACT: Vitamin D deficiency (VDD) has pandemic proportions worldwide. Numerous studies report on high prevalence of VDD in sunny regions like Near East and North Africa (NENA). Previous studies indicated that Libyan population was at risk of VDD. To contribute to the body of evidence, measurement of vitamin D status on children, adults, in Misurata region was conducted, and confirmed with validated dietary intake study. Serum 25(OH)D was analysed using electrochemiluminescence protein binding assay. Existing Food Frequency Questionnaires (FFQ) were adapted to Libyan Women Food Frequency Questionnaire (LW-FFQ). Repeated 24 h dietary recalls and LW-FFQ were employed in vitamin D intake evaluation. LW-FFQ was validated using 24 h dietary recall and vitamin D status as referent methods. The questionnaires included anthropometry and lifestyle information. Vitamin D status assessment revealed inadequate levels (25(OH)D < 50 nmol/l) in almost 80% of participants. Women (25-64 y) were identified as the most vulnerable group with vitamin D inadequacy present in 82% (61.6% had 25(OH)D < 25 nmol/l, and 20.2% had 25–50 nmol/l 25(OH)D). Average Vitamin D intake within the study sample ( n  = 316) was 3.9 ± 7.9 µg/d, with 92% participants below both Institute of Medicine (IOM) (10 µg/d) and European Food Safety Authority (15 µg/d) recommendations. Measured vitamin D status, in 13% of this group, correlated significantly ( p  = 0.015) with intake estimates. Based on self-report, consumption of vitamin D supplements does not exist among study participants. Additional lifestyle factors influencing vitamin D status were analysed. Only 2% of study participants spend approximately 11 min on the sun daily, 60.4% were obese, 23.1% were overweight and 71.2% reported low physical activity. These findings confirm previous reports on high prevalence of VDD in women across NENA, and in Libya. The situation calls for multi-sectoral actions and public health initiatives to address dietary and lifestyle habits.